PERAN BIMBINGAN DAN KONSELING UNTUK MENINGKATKAN KEMATANGAN KARIR SISWA MEMASUKI ERA SOCIETY 5.0 [THE ROLE OF GUIDANCE AND COUNSELING TO IMPROVE STUDENTS’ CAREER MATURITY ENTERING THE SOCIETY 5.0 ERA] - Fauziah, Febriella; Iswari, Mega; Daharnis, D (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2022)
This study discusses the role of guidance and counseling to improve the career maturity of students entering the era of society 5.0. The method used by the researcher is a literature study which examines based on journals and books. School is one of the institutions that spearhead the success or failure of achieving national education goals. Schools have an important role in developing students' potential. One that has a role in the career development of students in schools is guidance and counseling. One of the fields of guidance and counseling is career guidance which has the role of preparing competent students and ready to compete according to the times. Through career guidance, it can become a bridge for students to get closer and get to know the world of work and the things that must be prepared to enter the free market world, so that students are able to increase career maturity in order to plan the careers needed in the era of society 5.0.